An Analysis of the Impact of AI on Supply Chain Management: A Case Study of Amazon - Bhawni Talwar; Naresh Sachdev (Journal of Advanced Research in Service Management, 2024)
The worldwide level of competition has increased significantly with the growth and development of information technology. Numerous businesses have predicted that the introduction of artificial intelligence (AI) will cause significant changes in supply chain management (SCM) and operations in the future, including planning, scheduling, optimisation, and transportation. In terms of supply chain management, people will become increasingly interested in AI, machine learning, and other intelligent technologies. This specific research study gives a general review of the concepts of AI and SCM in this context. After that, the emphasis shifts to the timely and critical analysis of supply chain applications and research driven by AI. The developing AI-based business models of many case companies are examined in this exploratory study. Their applicable AI solutions and associated business values are also assessed. Consequently, this study pinpoints multiple domains of value generation for the integration of artificial intelligence inside the supply chain. Additionally, it suggests a method for creating business models for supply chain AI applications.